(untitled) - Bratcher, Suzanne (Mahwah, 1997)
This text models for teachers how to help children learn and write by establishing comfort with writing, building confidence, and developing competence. Several themes run through the learning-to-write-process presented in this text: writing is communication; writing is a powerful tool for learning
Keywords: English language,Tiếng Anh; Composition and exercises,Study and teaching (Elementary),Thành phần và các bài tập; Học tập và nghiên cứu (Tiểu học); United States,Hoa Kỳ